The effect of ligament size on the thermal fatigue life of 9Cr1Mo steel boiler header under cold, warm and hot starts. (March 2019) - Vetri Selvan, R.; Sathiya, P.; Devakumaran, K.; Ravichandran, G.
Abstract: The finite element (FE) simulations for the evaluation of thermal fatigue life of 9Cr1Mo steel boiler header is presented. Boiler headers experience load fluctuation during operation which leads to a significant magnitude of stress being experienced at the ligament region between two stubs in the header. The effect of load fluctuation during cold, warm and hot start on the peak stress has been computed for different ligament sizes. The stress magnitude is found to increase as the ligament size is decreased. When the thermal stress magnitude exceeds the yield strength of the material, it results in plastic deformation. From the cyclic variation of the stress and strain due to load fluctuations, the thermal fatigue life computed based on the Coffin-Manson relation. A reduction in the circumferential radial angle between stubs in the header is found to result in a reduction of thermal fatigue life. Graphical abstract: Highlights: The effect of ligament size on thermal fatigue of header was analyzed under cold, warm and hot start conditions. The decrease in the radial angle between stubs in the header increases the severity of thermal fatigue damage. The thermal fatigue life is lower in small ligament size and in cold start condition.